ANALYSIS OF THE EFFECTIVENESS OF USING PSYCHOLOGICAL TESTS FOR RECRUITMENT OF PROSPECTIVE TNI OR POLRI CADETS - Billy Martasandy (Adisam Publisher, 2024)
Research purposes This for-know analysis effectiveness use test psychology for recruitment candidate TNI cadets or National Police. The method used is qualitative, with a study field. As for the participants in the study, these are two prospective TNI and POLRI cadets. Research result This use of test psychology in recruitment of prospective TNI cadets or National Police is effective and useful in choosing individuals who are qualified, competent, and have integrity to join an organisation, whether military or police. Test psychology helps in evaluating various aspects of personality, motivation, and mental readiness, as well as ensuring that recruited members have appropriate moral and ethical values that meet the demands of their profession.